THE EFFECT OF USING CLUSTERING TECHNIQUE ON STUDENTS’ ABILITY IN WRITING RECOUNT TEXT ON THE X CLASS OF SMA SWASTA DARUL IMAN IN ACADEMIC YEAR 2021/2022 - KARTINI; MERI VANCITO; SABRUN JAMIL (Tuwah Pande: Jurnal Ilmu Pendidikan dan Pengajaran, 2023)
This study deals with the effect of using clustering technique on students’ ability in writing recount text on the X class of SMA Swasta Darul Iman Academic Year 2021/2022. Its objective is to find out whether the use clustering technique has a significance effect in writing recount text. Population used in this study of class X were 64 and samples used in this study were32 students. The method used in this study is an experimental method with a one group as pre-test and post-test design .This study was carried on using quantitative method. The data was analysed by using t-test. The researcher found the pre-test mean = 54,69 , deviation standard = 5,07 and experienced an increase in the post-test mean = 82,81 deviation standard = 3,09.From this analysis, writer found that guided clustering technique has significance in teaching writing recount text. It can be proved by the result of the analysis showed that “ ” observed about 26,78 was higher than “ttable” about 2,040 with the level significance is 0,05% it implies that the teacher of English should use clustering technique in teaching writing recount text so that the teaching and learning process can be successful.